Resistance training and endurance performance: physiological adaptations and recommendations for performance enhancement - Bentley, D.; Deakin, G.; McNaughton, L. R. (Routledge handbook of ergonomics in sport and exercise, 2016)
Athletes, coaches and sports scientists typically define training into two distinct areas: weight or resistance training, and aerobic or cardiovascular training. Traditionally, the former is taken to be the realm of the athlete and the latter the realm of the health-conscious individual, though clearly each are used by both groups of individuals. The ability of all humans, however, to perform activities of daily life is clearly related to maintenance of the main elements of health-related physical fitness; for example, aerobic capacity, strength and power production, and mobility (Faulkner and Eston, 2007; Fleg et al., 2005; Stathokostas et al., 2004). These fitness parameters can be positively modified with specific training objectives that may differ between resistance or endurance training modes.